2015
DOI: 10.11609/jott.o3298.6833-5
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery of Syzygium kanarense (Talbot) Raizada (Myrtaceae) - an endemic species of the Western Ghats, India

Abstract: Acknowledgements:We thank the Ministry of Environment and Forests for the financial assistance for the floristic explorations under the scheme assistance to Botanical Gardens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Later on, in the year 1996, Nayar reported that S. kanarense was considered as a critically endangered species and last seen by Talbot discounting the collection of R. Sundararaghavan. After a long period of 47 years, this plant has been rediscovered from evergreen forests and belongs to the Myrtaceae family (Shenoy et al, 2015). Still, no data available in S. kanarense plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, in the year 1996, Nayar reported that S. kanarense was considered as a critically endangered species and last seen by Talbot discounting the collection of R. Sundararaghavan. After a long period of 47 years, this plant has been rediscovered from evergreen forests and belongs to the Myrtaceae family (Shenoy et al, 2015). Still, no data available in S. kanarense plant species.…”
Section: Introductionmentioning
confidence: 99%
“…The flowers are white, 0.6-0.8 cm across, nearly sessile, buds globose, creamish white. The fruit is up to 2×1.2 cm with single seed, purple in color when mature, pulpy and crowned with the persistent calyx [1]. S. kanarense was described by Talbot in 1897 from the evergreen forests of the Gerusoppa Ghat in the North Kanara district of Karnataka.…”
mentioning
confidence: 99%
“…S. kanarense was described by Talbot in 1897 from the evergreen forests of the Gerusoppa Ghat in the North Kanara district of Karnataka. The species was collected again in 1964 after a gap of 67 years, by R. Sundararaghavan from the Hulical Ghat forests of the adjoining Shimoga District in Karnataka [1]. Nayar (1996) considers this as a critically endangered species and to have last been seen by Talbot discounting the collection of R. Sundararaghavan [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation